THE INFLUENCE OF BABAR SARI WATER QUALITY IN PLANNING ECO-TECH-EDU TOURISM AL AMIN LIVING LAB AND INDUSTRIAL PARK - Hendra Fahruddin Siregar; Rahmadhani Fitri; Novalinda (International Forum of Researchers and Lecturers, 2023)
Rivers are places, containers, and networks of water irrigation from springs to estuaries. The existence of rivers with their nature that flows from upstream to downstream has the potential for opportunity value and externality effects between upstream and downstream or along river flows (Pangesti, 2000). Eco-Tech-Edu Tourism Combination and integration of learning across applicable programs, the flow of the Babarsari river looks clear and flows well, so this is used in the construction of living labs and industrial parks. In its use as ecotourism, it is necessary to analyze the burden of pollutants. In determining the burden of pollutants, it is necessary to carry out water analysis and water status analysis based on the Decree of the Minister of Environment no. 115 of 2003 concerning guidelines for water quality status.